2024
DOI: 10.1029/2023ja032287
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Electron Precipitation Driven by Mesoscale Transients, Inferred From Ground and Multi‐Spacecraft Platforms

A. V. Artemyev,
X.‐J. Zhang,
A. G. Demekhov
et al.

Abstract: Precipitation of relativistic electrons into the Earth's atmosphere regulates the outer radiation belt fluxes and contributes to magnetosphere‐atmosphere coupling. One of the main drivers of such precipitation is electron scattering by whistler‐mode waves. Such waves typically originate at the equator, where they can resonate with and scatter sub‐relativistic (tens to a few hundred keV) electrons. However, they can occasionally propagate far away from the equator along field lines, reaching middle latitudes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 203 publications
1
1
0
Order By: Relevance
“…Figures 8c and 8d show the resultant pitch-angle diffusion rates at the loss cone and precipitating-to-trapped flux ratios, respectively, as a function of energy and maximum magnetic latitude (for a finite wave power) for these whistler-mode wave settings. Again, simulation results confirm the resonant energy estimates: to scatter relativistic (∼1 MeV) electrons waves should propagate to 30 40°magnetic latitude (see further discussion in Artemyev et al (2024)).…”
Section: Discussionsupporting
confidence: 73%
“…Figures 8c and 8d show the resultant pitch-angle diffusion rates at the loss cone and precipitating-to-trapped flux ratios, respectively, as a function of energy and maximum magnetic latitude (for a finite wave power) for these whistler-mode wave settings. Again, simulation results confirm the resonant energy estimates: to scatter relativistic (∼1 MeV) electrons waves should propagate to 30 40°magnetic latitude (see further discussion in Artemyev et al (2024)).…”
Section: Discussionsupporting
confidence: 73%
“…More recent simulation studies demonstrated that ducted waves and resultant propagation to higher MLATs are required to cause sub-relativistic/relativistic electron microbursts (Chen et al, 2022;Miyoshi, Oyama, et al, 2015;Miyoshi et al, 2020). By ground-based measurements of whistler-mode waves and satellite observations of the electron precipitation, Artemyev et al (2024) suggested that relativistic electrons are scattered…”
Section: Discussionmentioning
confidence: 99%